(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
This paper examines the transformative impact of e-commerce on business models and consumer behaviour. It explores how technological advancements and evolving consumer demands have driven the shift from traditional practices to e-commerce. While acknowledging the challenges faced by e-commerce, particularly in developing markets, the paper emphasizes the importance of infrastructure improvement, digital literacy promotion, regulatory streamlining, and technological innovation for sustained growth. Finally, it highlights the potential of emerging trends like mobile commerce, AI personalization, and sustainability to shape the future of e-commerce and unlock its full potential in the global marketplace.